A Critical Companion to Robert Zemeckis - Barkman, Adam; Sanna, Antonio (Lexington Books, 2020)
A Critical Companion to Robert Zemeckis offers a comprehensive, academic and detailed study of the works of Robert Zemeckis, whose films include successful productions such as the Back to the Future trilogy (1985-90), Forrest Gump (1994), Contact (1997), Cast Away (2000) and The Polar Express (2004), but also lesser known films such as I Wanna Hold Your Hand (1978), Used Cars (1980), and Allied (2015). Most of Zemeckis’ major productions were not only successful when they were first released but continue to enjoy popularity—with critics and fans alike—even today. This volume investigates several distinct areas of Zemeckisʼ works and addresses the different approaches: the philosophical, the artistic, the socio-cultural, and the personal. The methodologies adopted by the contributors differ significantly from each other, thus offering the reader a variegated and compelling picture of Zemeckisʼ oeuvre, which includes nineteen films. Contrary to the few volumes published in the past on the subject, the chapters in this volume offer specific case studies that have been previously ignored (or only partially mentioned) by other scholars. A Critical Companion to Robert Zemeckis offers a great variety of interdisciplinary approaches to Zemeckis’ films, illuminating, re-reading and/or interpreting for the first time the entire career of the director, from his first films to the most recent ones.